Progress in Preparation, Functional Characteristics and Application of Soybean Protein Amyloid-like Fibrils - ZHU Xiuqing, HAN Tianlu, LIU Jiyuan, GUO Ruqi, ZHU Ying, HUANG Yuyang, LIU Linlin (Shipin Kexue)
Soybean protein has high nutritional value and excellent functional characteristics, which has attracted much attention in the food industry, and is often used to improve the processing performance and nutritional value of foods. However, the functional characteristics of natural soybean protein are only limitedly applied, which cannot meet the needs of food processing, so modification of soybean protein has become a research focus. Modification technologies such as heat, high pressure and enzymatic treatments have been widely used and breakthroughs have been made. Soybean protein monomer or polypeptides can self-assemble and aggregate into amyloid-like fibrils under acid and high temperature conditions, resulting in changes the solubility and gelation properties of soybean protein. To enhance our understanding of recent progress in soybean protein amyloid-like fibrils (SPAF), this paper reviews the preparation methods and the formation mechanism of SPAF analyzes the influence of processing conditions on SPAF, and outlines the functional characteristics of SPAF such as solubility, gelation, foaming and emulsification properties. Furthermore, this review summarizes the application of SPAF and gives an outlook on future development in this field. It is our hope that this review will provide a reference for the application of SPAF in the food field.